Prevalence of Peripheral Vascular Disease in Diabetic Foot Infections and its Effect on Management Outcome (Journal of Bangladesh College of Physicians and Surgeons, 2019)
Background: Foot infection is a common problem affecting diabetics. Ischemia is a major factor contributing to progress and morbidity of the disease. The prevalence of peripheral vascular disease is higher in diabetics with faster progression.Aim: This study aimed to observe the prevalence of peripheral vascular disease in patients with diabetic foot infections presenting to this tertiary care centre.Methods: This prospective observational study evaluated 250 patients with diabetic foot infection admitted to Ibrahim Medical College and BIRDEM General Hospital, Dhaka, from 1st January 2015 to 31st December 2015.Total 72 patients were selected for Duplex study of lower limb vessels, Ankle Brachial Pressure Index (ABPI) and Pulse oxymetrywhich established the diagnosis of peripheral vascular disease and all patients were treated according to the standard protocol.Results: Of the 72 patients peripheral vascular disease was found in 25 patients (34.7%) and majority of them (88%) had distal below the knee vessel stenosis. There was significant correlation with older age (75%) and history of tobacco use (64%). The clinical presentations and outcomes such as hospital stay, healing time, pain were worse in individuals with peripheral vascular compromise on Duplex study of lower limb vessels, ABPI and pulse oxymetry.Conclusion: In this study we observed that significant number of diabetics presenting with foot infections have underlying peripheral vascular disease .The patients might not all be symptomatic or show obvious signs of PVD but need to be investigated for the same. Early detection of peripheral vascular disease in patients presenting with diabetic foot infection, using Duplex study,ABPI and Pulse oxymetrywith routine clinical and laboratory assessment can be of great value in long term care of these individuals.J Bangladesh Coll Phys Surg 2020; 38(1): 12-17